A Review of The Mashlahah of Uang Panai’ in Decision Making: The Role of Financial Behavior, Social Strata, Education and Religiosity - Kurniati; Indriyani MS, Eka (Fakultas Syariah Institut Agama Islam Negeri Palu, 2024)
The tradition of uang panai’ has been rooted in the Makassar Bugis tribe's marriage until now giving birth to several meanings, the higher the uang panai’ given shows the higher the Social strata of the family. Another meaning is also said to be that if there is no uang panai’ then there is no marriage. This tradition affects people's behavior in deciding to get married. Perhaps some of them choose to continue their relationship through silariang (elopement) and even commit suicide because they are frustrated that they cannot meet the demand for uang panai’. This paper examines community behavior in making decisions on the amount of uang panai’ influenced by financial behavior, Social strata, education and religiosity. This research uses a mixed method approach by using SMART-PLS data analysis and analyzing qualitatively with mashlahah analysis. The sampling technique is non-probability sampling with a purposive sampling method by taking samples based on certain criteria and selecting subjects according to the right informant. The results showed that financial behavior does not affect decision-making. The stronger the financial behavior of the community, the less likely the decision to meet the demands of the amount of money panai'. This is in line with the theory of planned behavior, the decision is to make considerations by making specific plans. Religiosity also does not influence decision-making. The stronger one's religious beliefs, the weaker the decision to fulfill the demands of panai'. This religious belief fosters responsibility so it is cautious in making decisions. The description of community behavior towards panai' money decision-making is more appropriate to explain in the concept of mashlahah mursalah.